EMPOWERMENT OF YOUTH COMMUNITY IN POSO REGENCY, THROUGH PRODUCE TOMATO AND MELON BY HYDROPONIC SYSTEM - Yosephine Sri Wulan Manuhara; Alfinda Novi Kristanti; Sugiharto Sugiharto; R. Djarot Sugiarso; Yohanes Kartjito Putro; Arga Wal Yudha (Faculty of Vocational Studies, Universitas Airlangga, 2022)
Background: Tentena City is one of the tourist centers with rapid economic growth located in Poso Regency because Poso Lake is very famous and able to change the economic level of the community. But there are still 20% of people who live very poor and 60% of the lower middle class and the remaining 20% of the middle to upper middle. Through the youth community Pukat Tentena is expected to foster and encourage millennials to develop vegetable and fruit entrepreneurs using more modern cultivation techniques. Objectives: empowering the youth community in Tentena city, Pamona Puselemba Subdistrict, Poso Regency, Central Sulawesi with entrepreneurial tomato fruit products and melons produced by hyrdoponik drip irrigation system. Methods: This community service activity was carried out in Tentena village, Pamona Puselemba Subdistrict, Poso Regency, Central Sulawesi Province with TENTENA PUKAT Youth Community partners starting from May to September 2021. Results: Mitra has successfully cultivated tomato and melon plants with hydroponic drip irrigation system techniques in green houses until they are obtained salesable results. The average number of tomatoes per stalk is 4.05 and the average fruit diameter is 5.1 cm; While the average weight of melons is 1.2 -1.8 kg. Conclusion: The results of this community service activity provide benefits for partners, namely providing additional knowledge about how to cultivate tomatoes and melons with hydroponic drip irrigation system techniques and increase partner income by selling tomatoes and melons from hydroponic cultivation.